Place and Importance of Electronic Evidence in Criminal Proceedings - Dilbandyan, Samvel (Bulletin of Yerevan University C: Jurisprudence, 2022)
This article is devoted to the place and importance of electronic evidence in criminal proceedings. Today, electronic information occupies a significant place in the complex process of solving crimes, which has simplified the solving of crimes. Legal regulation of the collection, verification and evaluation of electronic information by criminal procedure legislation is necessary for their effective use. The lack of legal regulation of many issues within the framework of the current criminal procedure legislation casts doubt on the reliability of this information.
Keywords: criminal process; evidence; crime detection; emails